Esponja Fibrilar de Fluoreto de Polivinilideno Enriquecida com Óxido de Grafeno Reduzido no Reparo de Defeito Ósseo Experimental em tíbia de Ratos - Jardim, Paulo Henrique de Affonseca (2022)
JARDIM, P.H.A. Fibrillar polyvinylidene fluoride sponge enriched with reduced graphene oxide in the repair of the experimental bone defect in rat tíbia. 2022. Doctorate - Graduate Program in Veterinary Sciences. Faculty of Veterinary Medicine and Animal Science, Federal University of Mato Grosso do Sul, Campo Grande, MS, 2022. Recent studies with polyvinylidene fluoride (PVDF) and reduced graphene oxide (rGO) demonstrate promising results in bone repair. The aim of this study was to evaluate the use of PVDF associated with rGO in the repair of unilateral monocortical bone defects performed in the tibia of rats. Ninety animals were divided into 3 groups of 30: DEF (Control), PVDF and PVDF/rGO, which in turn were subdivided according to the evaluation time (10, 20 and 30 days). The DEF group was submmited only to the bone defect and received no treatment. The other groups were submmited to the bone defect and treated as follows: defects filled with polyvinylidene fluoride = PVDF and defects filled with polyvinylidene fluoride enriched with reduced graphene oxide = PVDF/rGO. For the analyses, serum alkaline phosphatase (ALP) and bone alkaline phosphatase (FAO) estimates were performed, as well as histological estimates of the defect region according to the evaluation time. The PVDF and PVDF/rGO groups showed higher levels of bone alkaline phosphatase at 20 and 30 days after surgery when compared within their group and at 30 days when compared with the DEF group. Histological analyzes demonstrated, at 20 days, a greater neoformation of bone tissue in the DEF group when compared to the PVDF/rGO group, a greater presence of osteoblasts in the DEF group compared to the PVDF and PVDF/rGO groups, as well as a greater presence of inflammatory infiltrate in the PVDF group /rGO than to the DEF and PVDF groups. At 30 days of evaluation, a large number of multinucleated giant cells was observed, as well as an intense periosteal reaction in the PVDF/rGO group. With the help of weighted statistical analyzes (P<0.05) it is concluded that the PVDF and PVDF/rGO biomaterials increase the levels of bone alkaline phosphatase at 20 and 30 days of estimates. The use of PVDF and PVDF/rGO biomaterials did not accelerate the bone repair process compared to the DEF group. The PVDF/rGO biomaterial promoted great formation of multinucleated giant cells. Keywords: Bone consolidation, piezoelectricity, veterinary surgery, nanomaterials, solution blow spinning.